COVID-19 clinical outcomes by patient disability status: A retrospective cohort study. Issue 2 (April 2023) - Deal, Jennifer A.; Jiang, Kening; Betz, Joshua F.; Clemens, Gwendolyn D.; Zhu, Jiafeng; Reed, Nicholas S.; Garibaldi, Brian T.; Swenor, Bonnielin K.
Abstract: Background: People with disabilities might experience worse clinical outcomes of SARS-CoV-2 infection, but evidence is limited. Objective: To investigate if people with disabilities requiring assistance are more likely to experience severe COVID-19 or death. Methods: Data from the Johns Hopkins COVID-19 Precision Medicine Analytics Platform Registry (JH-CROWN) included 6494 adult patients diagnosed with COVID-19 and admitted between March 4, 2020–October 29, 2021. Severe COVID-19 and death were defined using the occurrence and timing of clinical events. Assistive needs due to disabilities were reported by patients or their proxies upon admission. Multivariable-adjusted Cox proportional hazards models were used to examine the associations between disability status and severe COVID-19 or death. Primary models adjusted for demographics and secondary models additionally adjusted for clinical covariates. Results: In this clinical cohort (47–73 years, 49% female, 39% Black), patients with disabilities requiring assistance had 1.35 times (95% confidence interval [CI]:1.01, 1.81) the hazard of severe COVID-19 among patients <65 years, but not among those ≥65 years, equating to an additional 17.5 severe COVID-19 cases (95% CI:7.7, 28.2) per 100 patients. A lower risk of mortality was found among patients <65 years, but this finding was not robust due to the small number of deaths. Conclusions: People with disabilities requiring assistance aged <65 years are more likely to develop severe COVID-19. Although our study is limited by using a medical model of disability, these analyses intend to further our understanding of COVID-19 outcomes among people with disabilities. Also, standardized disability data collection within electronic health records is needed.